Pengaruh Intensitas Aset Tetap Dan Pertumbuhan Penjulan Terhadap Penghindaran Pajak - Annisa Ayu Asri; Endang Mahfudin (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to determine, analyze and describe the effect of fixed asset intensity and sales growth on tax avoidance. The method used in this research is descriptive verification method with a quantitative approach which is sourced from the annual report of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling technique was using purposive sampling technique. The data obtained were analyzed using descriptive statistical testing, classical assumption test, multiple linear regression analysis, determination coefficient test and hypothesis testing using t test and f test. This study used SPSS version 16 to process data. The results of this study indicate that (1) the intensity of fixed assets has no effect on tax avoidance (2) sales growth has no effect on tax avoidance. (3) the intensity of fixed assets and sales growth simultaneously has no effect on tax avoidance. Keywords: Fixed Asset Intensity, Sales Growth, Tax Avoidance